2016
DOI: 10.3892/ol.2016.4886
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells and microglia in the processes of glioblastoma multiforme invasive growth

Abstract: The development of antitumor medication based on autologous stem cells is one of the most advanced methods in glioblastoma multiforme (GBM) treatment. However, there are no objective criteria for evaluating the effectiveness of this medication on cancer stem cells (CSCs). One possible criterion could be a change in the number of microglial cells and their specific location in the tumor. The present study aimed to understand the interaction between microglial cells and CSCs in an experimental glioblastoma model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
11
0
3
Order By: Relevance
“…MMPs, CCL18, CCL22, CXCL12, IL10, TGFB, TNF, FasL, VEGF). [181][182][183][184][185] Pericytes Pericytes (PDGFRβ + , CD13 + , NG2 + , α-SMA + , Desmin + ) or Rouget cells are contractile cells located directly on small blood vessels, including capillaries, pre-capillary arterioles, and postcapillary venules. 186 The major functions of pericytes are formation of blood vessels, glial scars, and the BBB, capillary diameter, and cerebral blood flow (CBF) regulation, amyloid β clearance, and neuroinflammation suppression, and they at times exhibit stem cell-like properties.…”
Section: Role Of Neurovascular Unit In Ischemia and Glioma Astrocytesmentioning
confidence: 99%
“…MMPs, CCL18, CCL22, CXCL12, IL10, TGFB, TNF, FasL, VEGF). [181][182][183][184][185] Pericytes Pericytes (PDGFRβ + , CD13 + , NG2 + , α-SMA + , Desmin + ) or Rouget cells are contractile cells located directly on small blood vessels, including capillaries, pre-capillary arterioles, and postcapillary venules. 186 The major functions of pericytes are formation of blood vessels, glial scars, and the BBB, capillary diameter, and cerebral blood flow (CBF) regulation, amyloid β clearance, and neuroinflammation suppression, and they at times exhibit stem cell-like properties.…”
Section: Role Of Neurovascular Unit In Ischemia and Glioma Astrocytesmentioning
confidence: 99%
“…Similarly, Iba-1-positive cells with increased cellularity, either in or scattered around the tumor area ( Fig. 2G, N ), appeared to be reactive microglia 15 , 16 . Based on these histological and IHC results, we diagnosed the tumors as gliomas (n=4), including glioblastomas (n=3; Tables 2…”
mentioning
confidence: 81%
“…Similarly, Iba-1-positive cells with increased cellularity, either in or scattered around the tumor area (Fig. 2G, N), appeared to be reactive microglia 15,16 .…”
mentioning
confidence: 84%
“…Recent studies have shown that gliomas cause reduced caspase-3 activity in microglia via an iNOS-based mechanism, resulting in tumor growth. In addition, it is thought that microglia directly support cancer stem cell growth in glioblastoma multiforme, contributing to its aggressive progression and resistance to treatment [48].…”
Section: Microgliamentioning
confidence: 99%